READINESS ANALYSIS OF MERDEKA CURRICULUM IMPLEMENTATION IN MADRASAH IBTIDAIYAH BALI - Rusmayani Rusmayani; Badi'atussolihah Badi'atussolihah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2024)
Merdeka curriculum is one solution to overcome post-pandemic learning problems. In its implementation, the merdeka curriculum in madrasah is adjusted to the readiness of madrasah in their respective regions. The aim of this research is to describe the readiness of Madrasah Ibtidaiyah in implementing the merdeka curriculum. This research is descriptive qualitative, with location in 9 madrasahs in Denpasar City, 2 madrasahs in Tabanan Regency, and an madrasah in Gianyar Regency. Data was collected by interviews and then presented descriptively. The research results found that 1). 8 MIS and 1 MIN in Denpasar City, 1 MIS in Gianyar Regency and 2 MIS in Tabanan Regency have implemented the Merdeka Curriculum starting in the 2023/2024 academic year, for MIN the implementation has been at all levels, however for MIS there are still several levels that still use K13, 2). Teachers have received training/workshops/and socialization with different intensities, thus influencing the level of readiness of teachers in implementing the Merdeka curriculum, 3). Library learning resources according to the Merdeka Curriculum and activity supplements are inadequate and need to be improved.